2010
DOI: 10.5491/shaw.2010.1.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related Factors Associated with Upper Extremity Function in Workers

Abstract: ObjectivesThis study aimed to find gender distinctions in terms of the sociology of the population; to determine work-related factors; to analyze gender differences in daily living, work, sports, and art performances; and to identify gender-related factors that limited performance of daily living and work activities.MethodsA questionnaire was designed that included disabilities of the arm, shoulder, and hand (DASH), accident history, disease history, work duration at current workplace, marital status, job sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
2
5
1
Order By: Relevance
“…Functional limitations were related to work time, accident history, work duration, job satisfaction, physical demands, and job autonomy among men. Whereas functional limitations among women were related to job satisfaction and physical demands [18], in our study men who sometimes or never vs. always experienced meaningfulness at work, who sometimes vs. never perceived emotional demandsm and often vs. never perceived high work pace had higher risk of mobility limitations. Further, we found that work pace was observed to be preventive for mobility limitations among women.…”
Section: Discussioncontrasting
confidence: 70%
“…Functional limitations were related to work time, accident history, work duration, job satisfaction, physical demands, and job autonomy among men. Whereas functional limitations among women were related to job satisfaction and physical demands [18], in our study men who sometimes or never vs. always experienced meaningfulness at work, who sometimes vs. never perceived emotional demandsm and often vs. never perceived high work pace had higher risk of mobility limitations. Further, we found that work pace was observed to be preventive for mobility limitations among women.…”
Section: Discussioncontrasting
confidence: 70%
“…16,22 A significantly higher DASH score in women (24.0 versus 17.4; p<0.01; d=0.39) confirms the data found in the literature. 26,27 It could be explained by women's higher sensitivity to pain and the fact that they report functional incapacity more readily than men do. 28 Another hypothesis could be linked to the types of tasks performed depending on gender.…”
Section: Discussionmentioning
confidence: 99%
“…If three or more items are not answered, this score cannot be calculated. Total score were obtained by conversion to a 100-point scale [13,14,15].…”
Section: Quickdashmentioning
confidence: 99%